(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
يتناول هذا البحث التلف الحاصل للخلايا الشمسية نتيجةً لتعرضها للتشعيع بالإلكترونات. قمنا بتعريض هذه الخلايا لحزم من الإلكترونات ذات تدفق متغير لخلق عيوب فيها تلعب دوراً أساسياً كمراكز إعادة اتحاد غير مشعة (non-radiative recombination centers (. وسعينا لخلق نفس الظروف التي تتعرض لها الخلية الشمسية في الفضاء الخارجي, ثم درسنا التغيرات التي تطرأ على الخصائص الفولطية الضوئية لهذه الخلايا. بينت القياسات أن جهد الدارة المفتوحة لخلية شمسية GaAs يتغير بتابعية جرعة التشعيع الإلكتروني والتي تقع ضمن المجال: 2x1012elec.cm-2 < < 5x1015 elec.cm-2 ووجدنا أنه يساوي: Voc = 1.22-0.04 log V Voc = 2.39-0.12 log V لكل من منطقتي الانتشار وإعادة الاتحاد على الترتيب. وقد وجدنا أن كثافة تيار الدارة المقصورة Jsc تتغير مع تغير جرعة التشعيع الإلكتروني وفق العلاقة: mA.cm-2 Jsc =62.47-3.45 log يظهر تلف الخلايا الشمسية التي درسناها في تناقص الاستطاعة العظمى لها نتيجة تزايد . تم إجراء القياسات في مختبر الأوساط غير المنتظمة واللامتجانسة, جامعة بيير وماري كوري (باريس VI) فرنسا عام 2002, 2001 This article deals with the degradation of solar cells induced by electron irradiation. We have exposed GaAs solar cells to different doses of accelerated electrons to create defects, which play an important role as non-radiative recombination centers. We try to achieve the same conditions to which the solar cells are exposed to in outer space. We have studied the variation of the photovoltaic characteristics of these cells versus electron flux. We found out that the open – circuit voltage of GaAs solar cells varies with the electron irradiation dose j, which we varied in the interval: 2x1012 elec.cm-2 < j <5x1015 elec.cm-2 and we found out that: Voc = 1.22 - 0.04 log j V Voc = 2.39 - 0.12 log j V for both, the diffusion and the recombination zones respectively. The density of the short-circuit current has been measured and we found that the current varies with the electron irradiation dose, according to the relation: Jsc = 62.47 - 3.45 log j mA.cm-2 The degradation of solar cells appears from the decrease of the maximum power when () increases.